2007
DOI: 10.1089/dia.2006.0039
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Non–Model-Related Variability on Blood Glucose Prediction

Abstract: We showed how blood glucose prediction is severely affected by the inaccuracy in the input variables. Metabolic fluctuations, causing variability in insulin dynamics, also display important effects, but these are difficult to change. The inaccuracy of carbohydrate counting and the use of blood glucose meters appear to be the two main sources of error, which can be reduced through better patient education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…22,23 The meal carbohydrate content is assumed known to the patient through carbohydrate counting. [24][25][26] While the technique is only approximate and can be prone to inaccuracy, 27 it remains the key clinical strategy recommended to estimate the glycemic effect of meals for the purpose of adjusting insulin dosage. …”
Section: Discussionmentioning
confidence: 99%
“…22,23 The meal carbohydrate content is assumed known to the patient through carbohydrate counting. [24][25][26] While the technique is only approximate and can be prone to inaccuracy, 27 it remains the key clinical strategy recommended to estimate the glycemic effect of meals for the purpose of adjusting insulin dosage. …”
Section: Discussionmentioning
confidence: 99%
“…Meal carbohydrate content is assumed to be known with some error through carbohydrate counting [39][40][41]. While this technique is only approximate [42], it remains the key clinical method recommended to estimate the glycaemic effect of meals for the purpose of adjusting insulin dosage [5].…”
Section: Glucose Measurement Insulin Type and Mealsmentioning
confidence: 99%
“…5 Graff and colleagues 6 found that patients overestimated carbohydrate content at breakfast, on average, by +8.5% (range, -93% to +100%) and underestimated carbohydrate content at lunch, on average, by -28% (range, -97% to +43%). Kildegaard and associates 4 observed an average intraindividual variation of 30% for estimates of carbohydrate meal content. 4 Methods for better estimating carbohydrate and improving insulin dosages are under investigation.…”
Section: Introductionmentioning
confidence: 97%
“…Kildegaard and associates 4 observed an average intraindividual variation of 30% for estimates of carbohydrate meal content. 4 Methods for better estimating carbohydrate and improving insulin dosages are under investigation. 7 Establishing analytical performance of blood glucose meters (BGMs) is the subject of regulatory and clinical debate.…”
Section: Introductionmentioning
confidence: 97%